Two Fungal Infections of Inflatable Penile Prostheses in Diabetics. Issue 4 (7th October 2015) - Cotta, Brittney H.; Butcher, Michael; Welliver, Charles; McVary, Kevin; Köhler, Tobias
Abstract: Introduction: Penile prosthesis infections have decreased since the introduction of antibiotic‐coated implants. Infections that do occur can be from more rare and virulent organisms than the traditional skin flora historically implicated. Aim: In this report, we present two cases of inflatable penile prosthesis (IPP) infection from C andida organisms in insulin‐dependent diabetic patients. Methods: Case report with literature review. Main Outcome Measures: Resolution of the two cases. Results: Both patients were found to have insulin‐dependent diabetes. Both patients also presented with infection of the device with Candida species, with the implant pump adherent to their scrotal skin. Conclusions: This report supports the emerging literature that the flora of IPP infections is changing. We suggest considering adding antifungal agents to antibiotic coatings, dips, or washout solutions at the time of penile prosthesis surgery in diabetic patients.Cotta BH, Butcher M, Welliver C, McVary K, and Köhler T. Two fungal infections of inflatable penile prostheses in diabetics. Sex Med 2015;3:339–342.